2021
DOI: 10.1186/s12955-021-01743-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental health problems in frontline healthcare workers after the first outbreak of COVID-19 in China: a cross-sectional study

Abstract: Background More than 210,000 medical workers have fought against the outbreak of Coronavirus Disease 2019 (COVID-19) in Hubei in China since December 2019. However, the prevalence of mental health problems in frontline medical staff after fighting COVID-19 is still unknown. Methods Medical workers in Wuhan and other cities in Hubei Province were invited to participate a cross-sectional and convenience sampling online survey, which assessed the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 18 publications
6
49
0
7
Order By: Relevance
“…These findings call for pre-emptive action in offering effective mental health services (e.g., relaxation therapy, desensitisation, grief coping) to healthcare workers especially COVID-19 frontline workers, to help cope with the challenges associated with COVID-19 ( 14 , 44 ). These current findings are consistent with previous findings ( 17 , 45 , 46 ). In mainland China, the closest neighbour of Taiwan, a high prevalence of anxiety (53%), depression (56%), insomnia (79%), and PTSD (11%) was reported among medical workers ( 45 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings call for pre-emptive action in offering effective mental health services (e.g., relaxation therapy, desensitisation, grief coping) to healthcare workers especially COVID-19 frontline workers, to help cope with the challenges associated with COVID-19 ( 14 , 44 ). These current findings are consistent with previous findings ( 17 , 45 , 46 ). In mainland China, the closest neighbour of Taiwan, a high prevalence of anxiety (53%), depression (56%), insomnia (79%), and PTSD (11%) was reported among medical workers ( 45 ).…”
Section: Discussionsupporting
confidence: 94%
“…These current findings are consistent with previous findings ( 17 , 45 , 46 ). In mainland China, the closest neighbour of Taiwan, a high prevalence of anxiety (53%), depression (56%), insomnia (79%), and PTSD (11%) was reported among medical workers ( 45 ). A systematic review and cumulated meta-analysis of studies on the psychological states of Chinese medical staff during COVID-19 revealed that the medical staff exhibited a substantial prevalence of anxiety symptoms (27%), depression symptoms (26.2%), stress-related symptoms (42.1%), and sleep problems (34.5%) ( 46 ).…”
Section: Discussionsupporting
confidence: 94%
“… Wang et al, 2021 ), ( Wickens et al, 2021 ), ( Wolfson et al, 2021 ), ( Wolfson et al, 2021 ), ( Wong et al, 2021 ), ( Yan et al, 2021 ) Living alone/ isolation 13 5.14 (X. Chen et al, 2021 ), ( Cheng et al, 2021 ), ( Fang et al, 2021 ), ( Kang et al, 2021 ), ( Khoury et al, 2021 ), ( Lan et al, 2021 ), (Y an Liu et al, 2021 ), (Yu an Liu et al, 2021 ), ( Liu et al, 2020 ), ( Mistry et al, 2021 ), ( Nkire et al, 2021 ), ( Veldhuis et al, 2021 ), ( Wang et al, 2021 ) Lack of social support / community support 10 3.95 (Feng et al, 2021), ( Glenister et al, 2021 ), ( Hong et al, 2021 ), ( Kang et al, 2021 ), ( Khoury et al, 2021 ), (Yu an Liu et al, 2021 ), ( Nkire et al, 2021 ), ( Sun et al, 2021 ), ( Wang Liu et al, 2021 ), (H. Wang et al, 2021 ) Geographical location of cohort 10 3.95 ( Ganson et al, 2021 ), ( Glenister et al, 2021 ), ( Guo et al, 2021 ), ( Rashid et al, 2021 ), ( Kim et al, 2021 ), ( Rossell et al, 2021 ), ( Wu et al, 2021a ), ( Yan et al, 2021 ), ( Yasmin et al, 2021 ), (Yunus et al, 2021) Increase workload/ workload changes / working conditions 9 3.56 (J. …”
Section: Resultsmentioning
confidence: 99%
“…For those who were both medical care providers and who experienced the pandemic, occupational pressure and the conflict between personal safety and professional roles may lead to chronic symptoms of PTSD. A recent study by Guo et al showed that healthcare workers in Wuhan were more likely to suffer from anxiety and PTSD than those in other cities in Hubei province during the COVID-19 outbreak [ 22 ]. A cross-sectional survey conducted by Si et al, from February 23 to March 5, 2020 among 863 medical personnel in 7 provinces in China, found a 40.2% prevalence of significant PTSD symptoms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%